SMS – Operated Room Air-Conditioning Unit (Journal of Namibian Studies : History Politics Culture, 2022)
The main purpose of the study was to design and innovate the SMS-Operated Room Air – Conditioning Unit. this was done by installing an arduino inside the control panel of the WAC unit which is operates based on the short messaging system (SMS). For this study, the turning ON and OFF function of the WAC unit was done with by sending the appropriate keywords with the use of a mobile phone. The special feature of this device was its auto-reply in which the unit is programmed to notify the sender of the current status of the unit. The advantage of device is to allow the owner to turn ON and OFF the unit even at considerable distance for as long as there is a network signal in the area. In addition, the user is informed of the current status of the WAC unit. The study was conducted at Bohol Island State University Bingag Extension Campus during the academic year 2016-2017. The researcher used the experimental research design during the assembly and testing of the device and descriptive research design to determine its acceptability. There were thirty (30) respondents from BSIT and DIT major in Refrigeration and Air-Conditioning Technology who evaluated the acceptability of the device.  The data were collected using an observation guide to determine its functionality, and a questionnaire with five criteria such as functionality, convenience, safety, durability and cost, which consist of formulated questions with the corresponding rating for acceptability assessment. It was observed that the device was able to successfully switch ON and OFF from different locations and was able to successfully send a reply to the sender of the current status of the unit. Based on the tabulated data, the operation of SMS- Operated Room Air – conditioning unit is functional based on desired operation. The researcher collected the questionnaire and evaluated, analyzed and interpreted the data. The data of the acceptability showed that the device earned a general weighted mean of 3.33 which confirms that the device was highly accepted to the respondents. However, it was recommended to expand the scope of operation of the device to include the control of its temperature setting, timer, fan speed and air-swing.